PENGARUH INTERAKSI ANTARA PEMBERIAN BIOFOSFAT DENGAN PENGGUNAAN KULTIVATOR LOKAL UBI JALAR TERHADAP PERTUMBUHAN HASIL DAN KANDUNGAN GULA TANAMAN UBI JALAR - Marina, Ida (Pro-STek, 2022)
This study aims to examine the effect of the interaction between the administration of biophosphate and the use of local Jakar potato cultivars on the growth, yield and sugar content of sweet potato plants. The research method uses (RAK) 4 times. The 1st factor was Biophosphate (B), consisting of two levels: b1 (100 kg/ha biophosphate) and b2 (200 kg/ha biophosphate). The second factor was Sweet Potato Cultivar (K), consisting of three levels: k1 (cilembu), k2 (maja) and k3 (brass and white). Differences in treatment means were tested using Duncan’s multiple range test at the 5% level. The results showed that bophosphate and sweet potato cultivars had no interaction effect. Phosphate administration did not have a different effect on all growth and yield variables of sweet potato plants. The use of cultivars had no different effect on growth, yield and sugar content.